Analysis of the Influence of the Number of Workers, Population and Regional Levies on Regional Original Income - Majid, Alfi Aulia; Asmara, Kiki; Nisa, Fauzatul Laily (Jurnal Ekonomi & Bisnis, 2025)
This study examines the influence of the number of workers, population size, and regional retribution on Regional Original Revenue in Probolinggo City during the period 2009 to 2023. Although showing an upward trend, PAD in Probolinggo City remains relatively low compared to other regions in East Java. Using a quantitative time series approach, secondary data were analyzed through multiple linear regression using SPSS version 25. The regression model meets classical assumptions and is considered valid, with an R² value of 0.886. Partially, only the population variable has a significant effect. This indicates that population growth has the potential to expand the region's economic and fiscal base, while the contributions of labor and retribution remain limited due to the dominance of the informal sector and inefficiencies in the collection system. These findings highlight the need for policies aimed at strengthening the local economic structure, improving labor quality, and reforming the retribution collection system to support more sustainable PAD growth.